LEVELS OF HEAVY METALS PB AND HISTHOPATHOLOGY OF SPLEEN OF THE BALI CATTLE MAINTAINED IN SUWUNG DENPASAR LANDFILL - Putra, Wahyu Semadi; Berata, I Ketut; Kardena, I Made (Buletin Veteriner Udayana, 2018)
Bali cattle eats organic and inorganic waste in Suwung Denpasar landfill as source of feed.  The waste was suspected contaminated by heavy metals Pb. The aim of this study is to determine levels of heavy metals Pb and spleen histopathologic changes of bali cattle reared in Suwung Denpasar landfill. Spleen samples were collected from 5 cattle for examination of heavy metals Pb by Atomic Absorption Spectrofotometri method and histopathology preparations made by Hematoxilin-Eosin staining. The results showed the presence of heavy metal Pb contamination which varied of 1.5024 ppm, 1.5002 ppm, 2.0267 ppm, 2.0268 ppm and 0.6818 ppm. Microscopically, showed histopathological changes the form of depletion and proliferation of lymphoid cells.